Association of acute-phase proteins with feed intake in transition dairy cows, and factors affecting feed quality and digestibility - Brown, William Everett (Kansas State University, 2020)
Production performance of livestock is dependent upon adequate feed intake to meet metabolic demands, yet variations in health, metabolism, feed quality and feed digestibility can greatly influence an animal’s ability to consume and digest feedstuffs in order to reach their full potential. Using a large dataset in the first study, we analyzed plasma alpha-1-acid glycoprotein (AGP), an acute-phase protein, in 434 transition dairy cows to determine its association with dry matter intake (DMI), common blood inflammatory and metabolic biomarkers, and transition cow health disorders with an overarching goal of evaluating AGP as a diagnostic tool. The plasma AGP concentration increased after parturition to a peak at 14 d postpartum. There was a strong negative association between AGP and DMI, metritis, retained placenta, hyperketonemia and haptoglobin in the postpartum period, but overall diagnostic ability of AGP was marginal based on receiver operating characteristic analysis. Nonetheless, the ease of quantifying plasma AGP and the lack of association with metabolic biomarkers suggest it may be a useful tool to evaluate transition status in dairy cows. In the second study, a novel high-protein corn product (HPCP) was fed to high-producing, mid-lactation dairy cows and compared with canola and soybean meals, and all diets were balanced for lysine and methionine requirements. The HPCP decreased milk and milk component yields through reduced total tract apparent dry matter and crude protein digestibility, potentially due to Maillard product formation. However, confirming previous research, the canola meal performed similarly to soybean meal when lysine and methionine requirements were met. Finally, forage quality is of utmost importance in ruminant diets, and harvesting practices influence the quality of the forage delivered to the animals. In the third study, an innovative round hay baler equipped with knives that cut the hay as it enters the baling chamber was employed, reducing the particle size and potentially facilitating easier incorporation of hay into total mixed rations. In this study, pre-cutting alfalfa hay bales increased bale weight and density, but also slightly, but significantly, increased neutral- and acid-detergent fiber and lignin. When processing the pre-cut bales in a mixer wagon, time to reduce particle size was greater compared with tub-grinding normal bales, but less shrink occurred. The determining factor for impacts of pre-cutting hay bales is evaluation of the chemical composition of the processed hay which could be fed to livestock, and data analysis is currently underway. The fourth project seeks to understand factors impacting silage hygiene that potentially have health implications for ruminants. Soil contains numerous micro-organisms, including Clostridia spp., which is implicated in enteric diseases in ruminants. The study evaluates whether drive-over silage piles stored on soil introduce soil from equipment during the packing process, which may inadvertently introduce pathogens. Of primary interest, P increased for outer layers on soil pads, and Fe was greater at lower vs. medium elevations, both of which could be indicative of soil contamination. Overall, outer layers of silage had reduced nutritive quality, increased ash and mineral content, and decreased digestibility. Evidence for an effect of pad type on microbiological aspects was marginal or limited by low detectability. Overall, the work in this dissertation demonstrates the association of inflammatory biomarkers on dry matter intake, and the importance of digestibility and high-quality harvest methods on feed quality and digestibility for optimum animal performance.
Keywords: alpha-1-acid glycoprotein; pre-cut hay; silage hygiene; high-protein corn product